Determination of d-Orbital Populations in a Cobalt(II) Single-Molecule Magnet Using Single-Crystal X-ray Diffraction - Craven, Matthew; Nygaard, Mathilde H; Zadrozny, Joseph M; Long, Jeffrey R; Overgaard, Jacob (Inorganic chemistry, 2018)
The tetrahedral cobalt(II) compound (Ph P) [Co(SPh) ] was the first mononuclear transition-metal complex shown to exhibit slow relaxation of the magnetization in zero external magnetic field. Because the relative populations of the d orbitals play a vital role in dictating the magnitude of the magnetic anisotropy, the magnetic behavior of this complex is directly related to its electronic structure, yet the exact role of the soft, thiophenolate ligands in influencing the d-electron configuration has previously only been investigated via theoretical methods. To provide detailed experimental insight into the effect of this ligand field, the electron density distribution in this compound was determined from low-temperature, single-crystal X-ray diffraction data and subsequent multipole modeling. Topological analysis of the electron density indicates significant covalent contributions to the cobalt-sulfur bonds. The derived d-orbital populations further reveal a fully occupied d orbital, minor d orbital population, and nearly equal population of the d , d , and d orbitals. Notably, we find that an electrostatic interaction between Co(II) and one hydrogen atom from a thiophenolate group in the xz plane increases the energy of the d orbital, leading to the nearly equal population with d and strong magnetic anisotropy.